2018
DOI: 10.1029/2018jg004490
|View full text |Cite
|
Sign up to set email alerts
|

Global Pyrogenic Carbon Production During Recent Decades Has Created the Potential for a Large, Long‐Term Sink of Atmospheric CO2

Abstract: Fires play an important role in the terrestrial biosphere carbon cycle, not only through direct carbon release but also contributing to a potential long-term storage as pyrogenic carbon (PyC). PyC is formed through fires, and, because it may resist further biological and chemical degradation, is more stable in soil and sediment than original biomass. At the global scale, contributions of fires to both atmospheric CO 2 emissions and PyC accumulation are potentially large but difficult to estimate. Our analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…Although the conversion of non‐woody fuels to BC is less efficient, about 80% of BC produced within the margins of the Congo River Basin is derived from savannah, grassy‐type biomass, based upon current carbon emissions (Van Der Werf et al, 2017) and BC production estimates (Jones, Santín, et al, 2019) for the region. This agrees with earlier modeling efforts which show African savannah fires to be a significant source of fire‐derived carbon on a global scale (Wei et al, 2018). The Congo River exports an estimated 1.4 Tg‐C as DBC plus PBC each year (Table 1, Coppola et al, 2018), which suggests that the production of BC in the basin exceeds the amount of BC removed annually by the Congo River by an order of magnitude.…”
Section: Resultssupporting
confidence: 92%
“…Although the conversion of non‐woody fuels to BC is less efficient, about 80% of BC produced within the margins of the Congo River Basin is derived from savannah, grassy‐type biomass, based upon current carbon emissions (Van Der Werf et al, 2017) and BC production estimates (Jones, Santín, et al, 2019) for the region. This agrees with earlier modeling efforts which show African savannah fires to be a significant source of fire‐derived carbon on a global scale (Wei et al, 2018). The Congo River exports an estimated 1.4 Tg‐C as DBC plus PBC each year (Table 1, Coppola et al, 2018), which suggests that the production of BC in the basin exceeds the amount of BC removed annually by the Congo River by an order of magnitude.…”
Section: Resultssupporting
confidence: 92%
“…Importantly, there is little consistency between individual studies and the method employed to estimate PyC content generated during fire events, therefore the PyC production rate across studies was highly variable which creates challenges, particularly when modeling at larger spatial scale (Wei et al, 2018). By compiling published data of soil PyC content in the whole soil profile to estimate global PyC stock across a variety of environmental constraints (e.g., climate, soil pH, site net primary production), Reisser et al (2016) found that soil properties, rather than fire characteristics best explained PyC content at global scales where high clay soils (clay content over 50%) and alkaline soils had more PyC content than low clay soils and acidic soils.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have pointed to PyC generation as offsetting C emissions during wildfire (Wei et al, 2018;Jones et al, 2019) requiring us to further assess the influence of fire on the global C balance. Importantly, these studies demonstrate that PyC accumulation in ecosystems is most directly related to fire severity and frequency (Sawyer et al, 2018;Adkins et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with pyrogenic organic matter resulting from incomplete combustion of organic matter in heath and wood savanna leading to lower available N, which subsequently lowers the C:N ratio and immobilizes N [43]. Charcoal (pyrogenic carbon) from forest fires has been shown to change soil pH [44] and produce a significant long-term carbon sink [45,46]. Moreover, past research [47] has shown that the abundance of ericaceous plants, such as Kalmia, is negatively correlated with soil ammonium and phosphorus contents, leading to limitations in soil nutrient availability.…”
Section: Discussionmentioning
confidence: 52%